A survey on edible aroids consumed by locals in Kelantan, Peninsular Malaysia - Zulhazman, H.; Fizree, M. Asraf; Azahar, A. Muhamad; A. B., Mohd Fadzelly; Anis, A. Nazahatul (2021)
A total of seven variations of edible Araceae species were identically consumed by locals in the Districts of Kota Bharu and Machang, Kelantan, Peninsular Malaysia. These species are Keladi Pinang, Keladi Batang Putih, Keladi Tapak Badak, Keladi Birah, Keladi Batang Hitam, Keladi Candek and Keladi Tetawi. However, through a taxonomic identification were recognised only four species, these are Colocasia esculenta (L.) Schott, Alocasia macrorrhizos (L.) G.Don, Alocasia longiloba Miq. and Xantosoma sagitifolia (L.) Schott. The results revealed that Colocasia esculenta (L.) Schott Alocasia macrorrhizos (L.) G.Don. have three and two variations of species, respectively. The study also shows that Araceae is not only as sources of medicinal and ornamental but also commonly used by locals as foods which can be potentially explored and commercialized as a new bio-economy product.